Representation of Shamanism in the Film "The Medium" (Semiotic Analysis of Chaerles Sanders Pierce) - Putri, Tri Buana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Medium is a supernatural horror film, produced by Showbox from South Korea and GDH 559 from Thailand, directed by Banjong Pisanthanakun, who also serves as a producer alongside Na Hong-Jin, the director of the film The Wailing. This research aims to understand the presence of shamanism or witchcraft in Indonesia and Thailand, as well as the depiction of shamanism in Indonesia through the semiotics of Charles Sander Pierce, by connecting signs, objects, and meanings in accordance with what is portrayed in the film The Medium. This research uses a descriptive qualitative method with data collection techniques such as observation, analysis, and literature review, based on the semiotic analysis of Charles Sanders Pierce. The research findings show that shamanism in the Isan community in Thailand is portrayed as a bridge between humans and the supernatural world, with the shaman acting as a mediator. During the ritual process, the shaman uses various tools such as white thread, candles, incense, and statues. Mantras are used as a form of communication, the worship space serves as a place of worship, dance accompanied by music is a form of worship, ritual scars are a form of shamanic impact, the use of blood and cow heads is a way to ward off evil spirits, and traditional Thai clothing represents the local culture and traditions.